2002
DOI: 10.1021/la0117146
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Interior of Styrene−Maleic Anhydride Copolymer Aggregates Probed by Fluorescence Spectroscopy

Abstract: Several fluorescence techniques have been applied to characterize the aggregates of styrene-maleic anhydride copolymers (SMA). The formation of hydrophobic microdomains was confirmed by monitoring the I1/I3 ratios of pyrene dissolved in SMA solutions. Fluorescence quenching experiments indicate that protective quenching is occurring. The excimer-to-monomer ratio of di(1-pyrenylmethyl) ether and stoppedflow fluorescence measurements show that the interior of these SMA aggregates is extremely rigid, much more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 19 publications
5
41
0
Order By: Relevance
“…Second, the polymers do not adopt a random coil conformation at high pH, but they have a collapsed conformation at every pH value tested. This observed polymer conformation is in line with a previous study that showed that SMA copolymers with a 3:1 styrene/maleic acid contain hydrophobic domains in their polymer conformation as investigated by pyrene fluorescence (24). An increase in the styrene fraction of the polymer also leads to an increase in the number and/or sizes of the hydrophobic domains.…”
Section: The Sma 14:1 Variantsupporting
confidence: 91%
See 1 more Smart Citation
“…Second, the polymers do not adopt a random coil conformation at high pH, but they have a collapsed conformation at every pH value tested. This observed polymer conformation is in line with a previous study that showed that SMA copolymers with a 3:1 styrene/maleic acid contain hydrophobic domains in their polymer conformation as investigated by pyrene fluorescence (24). An increase in the styrene fraction of the polymer also leads to an increase in the number and/or sizes of the hydrophobic domains.…”
Section: The Sma 14:1 Variantsupporting
confidence: 91%
“…Indeed, in previous studies it was found that at low pH the 1:1 SMA variant collapses into a globular conformation that contains hydrophobic domains while the polymer is still water soluble (23). Such hydrophobic domains may occur within one polymer chain, but they also may be formed as a consequence of intermolecular interactions, when the polymers are present in aggregates containing multiple polymer chains termed ''polymeric micelles'' (24,25), as will be discussed later. Because the conformational state of the polymers is likely to be important for their interaction with lipid membranes, it was investigated how polymer conformation may be affected by the styrene/maleic acid and pH.…”
Section: The Number Of Charges Per Unit Length Of Polymer Determines mentioning
confidence: 90%
“…membranes, 1,11,14 polymeric micelles, 12,13,15,16,18,20 and polymer matrices 19 have all been investigated with DiPyMe. Considering such a sustained interest over a time period spanning more than three decades, it is thus somewhat surprising that the hydrolysis of DiPyMe in aqueous solutions has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic boronic acid and its functional derivatives, and some functionalized carboranes have become an very important class organic compounds, which are utilized in a variety of biological and medical applications, such as carbohydrate recognition [22], neutron capture therapy for cancer treatment as effective tumour-targeting agents [23,24], especially for brain tumours [25,26], and protease enzyme inhibition [27]. Kataoka et al [28][29][30][31][32] synthesized a novel water-soluble polymer with lectin-like function by introducing phenylboronates, as sugar -recognizing moieties, into the side-chain of poly (N,N-dimethylacrylamide) [28,29].…”
Section: Introductionmentioning
confidence: 99%